Geomorphology and Sediments of the Inner New York Bight Continental Shelf. - Williams,S. Jeffress; Duane,David B. (1974)
Approximately 445 miles of continuous seismic reflection profiles and 61 vibrating cores were obtained from the Inner New York Bight which encompasses about 250 square miles of the offshore from northern New Jersey and western Long Island. Report discusses geomorphology and shallow subbottom structure, surface and subsurface sediment characteristic and distribution, sediment origins, and sand needs and resource potential.